PENGARUH PRICE EARNING RATIO TERHADAP RETURN SAHAM DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Adila Puspita Dara; Pipit Mutiara (Jurnal Financia : Akuntansi dan Keuangan, 2021)
In the current era, if the structure and financial organization, corporate capital support each other and cooperate well with each other. Then the company's success can be achieved. This study aims to examine the effect of price earning ratio on stock returns, its impact on company size as an intervening variable in the food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange in 2014-2018. The data analysis technique used quantitative descriptive method. The results showed that there was no significant influence between price earning ratio, stock return and company size.